(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the formation processes and functional characteristics of sacred landscapes, emphasizing their role in the cultural heritage of humankind. The concept of a “sacred landscape” is analyzed in relation to religious and natural factors shaping its evolution. The study highlights the main functions of sacred landscapes—spiritual-philosophical, cultural-historical, ecological, and touristic-recreational. The findings demonstrate that sacred landscapes should be recognized as vital geographical systems ensuring cultural continuity and ecological sustainability.